Design and Implementation of Spatial Domain Technique in Steganography using RSA Encryption with Genetic Algorithm - Nanwal, Jyoti; Nanwal, Pooja (Indian Journal of Computer Science, 2017)
The usage of internet is increasing day by day and network security is becoming more important to us as the volume of data being exchanged is increasing. The data (i.e. secret data) transmitted by the sender can be detected, altered or modified in the network. In this paper, to prevent the data from being detected, we used modified Least Significant bit technique for hiding the data into bits of the image pixel and to prevent the data from being modified or altered, RSA encryption technique combined with Genetic algorithm was used as it would be very hard to break. We changed the least significant bit (LSB) to the nearest pixel according to the secret data bit so that it would be hard to find out the original message. In the present work, modified least significant bit embedding technique was used with genetic algorithm and encryption technique to get enhanced results or to get better results in terms of better security, image quality, PSNR ratio, and robustness. Encryption technique uses the concept of both public and private key to enhance the security level of the proposed work.Â